2019
DOI: 10.1039/c9tc04335g
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of the charge carrier dynamics of CH3NH3PbI3 perovskite crystallization process

Abstract: Although CH3NH3PbI3 perovskite has attracted enormous scientific attention over the last decade or so, important information on the charge extraction dynamics and recombination processes in perovskite devices is still missing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Dar et al 50 have shown that the MA-ordered domains (T < transition temperature) have larger bandgap than the MA-disordered domains (at the tetragonal phase), which is in agreement with our experimental results (Fig. 6) when comparing the orthorhombic with the tetragonal phase 48 . Also, the obtained blueshift of the absorption peak in the tetragonal phase is rationalized due to the thermal expansion of the CH 3 NH 3 PbI 3 lattice 54 .…”
Section: Temperature Dependent Tassupporting
confidence: 93%
See 1 more Smart Citation
“…Dar et al 50 have shown that the MA-ordered domains (T < transition temperature) have larger bandgap than the MA-disordered domains (at the tetragonal phase), which is in agreement with our experimental results (Fig. 6) when comparing the orthorhombic with the tetragonal phase 48 . Also, the obtained blueshift of the absorption peak in the tetragonal phase is rationalized due to the thermal expansion of the CH 3 NH 3 PbI 3 lattice 54 .…”
Section: Temperature Dependent Tassupporting
confidence: 93%
“…Kong et al 47 acknowledged that the high-energy peak can be attributed to the transitions of the freeexcitons, but he assigned the low-energy emission peak to the defects. Finally, Wehrenfennig et al 48 ascribed the obtained two emission peaks to coexisting tetragonal inclusions and the orthorhombic matrix at the lower temperatures. We believe that for the temperature below of 120 K we can detect the orthorhombic and the tetragonal phases, as well, because of the trapped tetragonal phases in the low temperature orthorhombic phase.…”
Section: Temperature Dependent μPlmentioning
confidence: 93%
“…To further explore the carrier dynamics of the photoactive layer with NCs and HTLs, transient absorption spectroscopy (TA) measurement [27][28][29][30] was performed, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 99%
“…The photoexcited state processes occurring within a supramolecular ensemble of D–A systems are influenced by numerous factors including the choice of chromophores, type of assembly, and consequent intra- and interchromophoric electronic coupling and reorganization energies of the D–A sytems along with the experimental conditions. A compendious picture of the free carrier generation dynamics in a specific D–A based photosystem calls for an integrated approach wherein both theoretical models and experimental tools are implemented to comprehend the complete sequence of stages, right from the design of a specific D–A system, process of self-assembly, fabrication of the OSCs followed by in situ monitoring of the excited state dynamics and free carrier generation. , Design of distinct donor–acceptor supramolecular architectures of covalently linked systems, correlating the ultrafast excited state dynamics to real time device performance and thereby developing strategies for optimizing the SMOSCs based device performance, necessitates further advanced theoretical and experimental investigations. Understanding the underlying photoinduced mechanisms in supramolecular assemblies integrating elements from supramolecular chemistry, crystallography, ultrafast spectroscopy, and the subsequent emergent properties has the potential to unfold unanticipated facets and open up new opportunities into the field of functional organic materials.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%